2020
DOI: 10.2147/nss.s271140
|View full text |Cite
|
Sign up to set email alerts
|

<p>Examining Sleep and Mood in Parents of Children with Sleep Disturbances</p>

Abstract: Objective The current study examined sleep and mood associations in parents of children with sleep disturbances across a sample of typically developing children and children with neurodevelopmental disorders. The mediating effect of children’s sleep on the relationship between parents’ sleep and mood was also assessed. The study explored differences in parents’ sleep based on whether 1) the child had a sleep disturbance, and 2) the child was typically developing or had a neurodevelopmental disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 41 publications
0
19
0
1
Order By: Relevance
“…Parents with a poor quality of sleep reveal greater cognitive or somatic arousal before sleeping when their children have sleep difficulties. Poor quality sleep by parents can be associated with chronic insomnia problems, and their mood is also mediated by their children’s quality of sleep 29 . Authors such as Mazza et al (2020) 19 analyzed and compared children’s self-perception about their sleep and estimates of the quality of sleep made by their parents, concluded that there are discrepancies between the two denoting insufficient agreement on sleep duration and night wakefulness 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Parents with a poor quality of sleep reveal greater cognitive or somatic arousal before sleeping when their children have sleep difficulties. Poor quality sleep by parents can be associated with chronic insomnia problems, and their mood is also mediated by their children’s quality of sleep 29 . Authors such as Mazza et al (2020) 19 analyzed and compared children’s self-perception about their sleep and estimates of the quality of sleep made by their parents, concluded that there are discrepancies between the two denoting insufficient agreement on sleep duration and night wakefulness 19 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, having a child with a sleep disorder can be a stressful event. Other research has shown that parents of children with sleep problems experience higher levels of insomnia [ 48 ]. Mothers and fathers with insomnia report children with sleeping disorders such as bedtime resistance, sleep duration, sleep anxiety, waking at night, and/or daytime sleepiness [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sınırlı sayıda çalışma, ebeveynliğe geçişte ebeveynlerde uykusuzlukla birlikte evlilikten alınan doyumun azalabileceğini ve uyku sorunu olan çocukların ebeveynlerinin uyku kalitelerinin de bozulduğunu göstermiştir. 15,16 Çalışmamızda, çocuklarında uyku sorunu ifade eden annelerin evlilik doyumu, uyku sorunu ifade etmeyen annelerin evlilik doyumundan farklı olmamakla birlikte gece daha sık uyanan bebeklerin annelerinin evlilik doyumunda azalma izlenmiştir. Benzer şekilde, Bernier ve ark.…”
Section: Discussionunclassified